Influence of Usability of Digital Population Identity Application on User Satisfaction at Dukcapil Sleman, Yogyakarta, Indonesia - Prisccillia Titis Kristy Ningrum; Rahmat Rian Hidayat; Arum Marwati; Anas Azhimi Qalban (Department of Informatics, Faculty of Science and Technology, UIN Prof. K.H. Saifuddin Zuhri, Purbalingga, Indonesia, 2026)
Sleman Regency recorded the highest activation rate of the Digital Population Identity (IKD) application in the Special Region of Yogyakarta at 13.07% as of February 2025. However, user complaints regarding system obstacles and complex activation processes persist on digital platforms. This study aims to determine how the usability dimensions of learnability, efficiency, memorability, and error handling influence user satisfaction at the Sleman Population and Civil Registration Agency (Dukcapil). Using a quantitative causal-associative approach, data were collected from 100 respondents through simple random sampling. A structured questionnaire of 32 items using a 5-point Likert Scale was distributed via Google Forms. Multiple linear regression analysis was employed to identify the specific influence of each usability dimension. Validity was assessed using the Pearson Product-Moment correlation, and reliability was confirmed using Cronbach's Alpha. The results indicate that usability dimensions significantly affect user satisfaction, with an F-value of 13.945 exceeding the F-table of 2.47, and a total contribution of 37% based on the coefficient of determination. Despite high satisfaction among digital natives, the study reveals critical areas for improvement in memorability and error aspects. Developers should prioritize optimizing server performance and simplifying the interface to minimize user errors and enhance inclusive satisfaction across all demographics.